PENGARUH INDONESIA AFRICA FORUM (IAF) TERHADAP PERLUASAN PASAR NON-TRADISIONAL INDONESIA DI KAWASAN AFRIKA - Saniah "; Umi O. Retnaningsih (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Market access is crucial to improve economic development through export activities. Indonesia has tried to expand its markets to the non-traditional ones. Africa is prospective to be the new market expansion due to its population number, product diversification, and interdependency. This research explains the reasons of why Indonesia established Indonesia Africa Forum (IAF) and the development of the initiatives.This qualitative research explains reasons of IAF establishment, actions, and progress. Content analysis using secondary data from books, journals, news from newspapers and televisions, official reports from Indonesia Ministry of Foreign Affairs, and websites was used to explore the data. Interdependence theory from Robert O. Keohane and Joseph S. Nye help to analyze from nation-state level of analysis.The research shows the Indonesia Africa Forum (IAF) have transformed Indonesia Economic development through market expansion in non-traditional market, i.e. 53 countries in Africa. IAF have achieved with 10 business deals and announcements. The Preferential Trade Agreement between Indonesia-Mozambique reduce tariff significantly since tariff is a big trade barriers. Better access to Africa is facilitated with flight transit in Addis Ababa. Key Words: Indonesia Africa Forum (IAF), Economic Diplomacy, Business Agreements and business announcement, Non-Traditional Market